Researching the sensitive issues - Identity in relation to one's sexuality - Gyasi-Gyamerah, A.A.; Fiaveh, D.Y.; Hiadzi, R.A. (University of Ghana, 2015)
Societies have different ideas about who we are and how we should express ourselves. These ideas are translated into the norms and values of the society and affect people's sense of id entity. Due to the cultural setting, some aspects of the Ghanaian's life that are paramount to identity construction including sexual preferences, sexual orientation, and fertility are sensitive areas that are rarely discussed. As such, it is very difficult researching into these areas. This pa per therefore looks at the theories that underlie researching into these sensitive areas, the methods used in collecting data, and the ethical protocols that undergird them from an African perspective. The paper ends on a reflective note as it deals with our experiences researching these areas using urban Ghanaian samples
School of social sciences colloquium
Keywords: researching; norms; cultural setting; collecting data